The representation of Asian-Americans amid COVID-19: A case study of The Washington Post and CNN - Ivanova, Anna (2023)
This paper focuses on the representation of the Asian-American community during the COVID-19 pandemic in the opinion articles of the US media about the growing expressions of violence against the community. These articles were posted in The Washington Post and CNN by an Asian-American journalist and an American journalist, respectively. Quantitatively, this study focuses on the proper nouns “Asian(s)” and “American(s)”. Qualitatively, it focuses on identifying patterns and interpreting the meanings underlying the discourse structures employed by each author. For these purposes, corpus linguistics and critical discourse analysis (CDA) were employed. Results show that the Asian-American author uses the proper nouns and rhetorical figures more than their American counterpart, who mostly uses quoting. This, since the former speaks from the community and the latter speaks to the community. It is suggested that the opinion articles discourse should be approached critically since they may influence the readers’ representations around the topic.